2022
DOI: 10.1161/strokeaha.121.034366
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Significance of Malnutrition Risk in Patients With Acute Ischemic Stroke: Results From the Third China National Stroke Registry

Abstract: Background and Purpose: To investigate the prevalence of malnutrition risk in patients with acute ischemic stroke (AIS) at admission, the association between malnutrition risk and long-term outcomes, and whether the predictive ability would be improved after adding to previous prognostic models for poor outcomes. Methods: Based on the Third China National Stroke Registry data from August 2015 to March 2018, we evaluated malnutrition risk using objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 39 publications
2
47
1
Order By: Relevance
“…Moreover, the incidence of moderate to severe malnutrition risk ranged from 7.0 to 33.7%. The prevalence of moderate to severe malnutrition in this cohort was higher than that previously demonstrated in Third China National Stroke Registry ( Zhang et al, 2021 ) and a hospital-based retrospective study in Japan ( Naito et al, 2020 ), as well as similar to that reported in Nanjing Stroke Registry Program ( Yuan et al, 2021 ). This discrepancy of variation in malnutrition prevalence may be attributed to the difference in nutritional screening tools, timing, and populations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the incidence of moderate to severe malnutrition risk ranged from 7.0 to 33.7%. The prevalence of moderate to severe malnutrition in this cohort was higher than that previously demonstrated in Third China National Stroke Registry ( Zhang et al, 2021 ) and a hospital-based retrospective study in Japan ( Naito et al, 2020 ), as well as similar to that reported in Nanjing Stroke Registry Program ( Yuan et al, 2021 ). This discrepancy of variation in malnutrition prevalence may be attributed to the difference in nutritional screening tools, timing, and populations.…”
Section: Discussionsupporting
confidence: 87%
“…Several objective nutritional tools were performed for evaluating malnutrition risk, including the controlling nutritional status (CONUT) score ( Ignacio de Ulíbarri et al, 2005 ), geriatric nutritional risk index (GNRI) ( Bouillanne et al, 2005 ), and prognostic nutritional index (PNI) ( Buzby et al, 1980 ). Recently, the three malnutrition scores, which can be easily calculated from objective variables, have been validated in predicting the prognosis of cardiovascular diseases and ischemic stroke ( Raposeiras Roubín et al, 2020 ; Yuan et al, 2021 ; Zhang et al, 2021 ). Using the three objective malnutrition indexes, data from Third China National Stroke Registry found that malnutrition risk in ischemic stroke patients was linked to a higher risk of long-term death and major disability ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Zhang et al reported that 1.95-5.89% of patients with acute ischemic stroke had a moderate to severe malnutrition risk. 28 Due to the inclusion criterion of the elderly population only, the proportion of END (33.2%) and moderate to severe malnutrition risk (4.6-21.4%) in our study were higher than in previous reports.…”
Section: Discussioncontrasting
confidence: 71%
“…Zhang et al performed a nationwide study and found that malnutrition was associated with long-term mobility and mortality in acute ischemic stroke. 28 The FOOD trial proved that ischemic stroke patients who were malnourished at admission had poor six-month prognoses. 29 It is recommended that enteral diets, nutritional supplements, and nasogastric tubes should be supplied for patients with malnutrition or those at malnutrition risk.…”
Section: Discussionmentioning
confidence: 99%